The Effect of The SPAWN Strategy on Developing Reading Comprehension Skills Among First-Year Middle School Students (Journal of the College of Basic Education, 2026)
The current research aims to identify "The Effect of the SPWAN Strategy on Developing Reading Comprehension Skills among First-Intermediate Grade Students." The researcher adopted the experimental method, as it is suitable and appropriate for the nature and objectives of the study. A quasi-experimental design was used, specifically the posttest-only control group design with random assignment. The research sample consisted of (61) students randomly selected from Al-Nawaris Secondary School, affiliated with the General Directorate of Education of Rusafa First in Baghdad Governorate, with (30) students in the experimental group and (31) in the control group. The researcher ensured equivalence between the two groups in variables such as chronological age (in months), parents' academic achievement, mid-year Arabic language grades for the academic year 2024/2025 (for the first intermediate grade), and pretest scores. The researcher personally taught both groups — the experimental group using the SPWAN strategy and the control group using the traditional method for 10 weeks. A reading comprehension test was developed by the researcher, consisting of (33) items distributed across four questions: 30 objective-type items and 3 essay-type items. The test was administered to both groups at the end of the experiment. The data was statistically analyzed using the SPSS program.The findings revealed:"There is a statistically significant difference at the (0.05) level between the mean scores of the experimental group and the control group, in favor of the experimental group."